Women in Doubt: Women's Representation in K-Drama Series Search: WWW - Tarisha Artya Andjani; Firly Annisa (Jogjakarta Communication Conference (JCC), 2024)
Korean film and drama serve as powerful mediums of mass communication, capable of portraying and depicting the realities inherent in the cultural and social fabric of Korean society.